2008
DOI: 10.1073/pnas.0710100105
|View full text |Cite
|
Sign up to set email alerts
|

COPI coatomer complex proteins facilitate the translocation of anthrax lethal factor across vesicular membranes in vitro

Abstract: The delivery of the diphtheria toxin catalytic domain (DTA) from acidified endosomes into the cytoplasm of eukaryotic cells requires protein-protein interactions between the toxin and a cytosolic translocation factor (CTF) complex. A conserved peptide motif, T1, within the DT transmembrane helix 1 mediates these interactions. Because the T1 motif is also present in the N-terminal segments of lethal factor (LF) and edema factor (EF) in anthrax toxin, we asked whether LF entry into the cell might also be facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 27 publications
2
46
0
Order By: Relevance
“…The LFn-DTa is a fusion protein consisting of the LF binding domain for PA and the C domain of diphtheria. Tamayo et al (2008) clearly demonstrated that the anthrax LFn-DTa fusion protein construct was translocated across the endosomal membrane in an ATP and cytosol dependent fashion, and this observation was confirmed by Dmochewitz et al (2011). Tamayo et al (2008) also demonstrated using GST-LFn pull downs that the T1 motif in anthrax lethal factor directly binds -COP, as well as zeta ( )-COP, and that a synthetic peptide containing the DT T1 motif blocked this interaction.…”
Section: β Cop Functions As a Ctfsupporting
confidence: 52%
“…The LFn-DTa is a fusion protein consisting of the LF binding domain for PA and the C domain of diphtheria. Tamayo et al (2008) clearly demonstrated that the anthrax LFn-DTa fusion protein construct was translocated across the endosomal membrane in an ATP and cytosol dependent fashion, and this observation was confirmed by Dmochewitz et al (2011). Tamayo et al (2008) also demonstrated using GST-LFn pull downs that the T1 motif in anthrax lethal factor directly binds -COP, as well as zeta ( )-COP, and that a synthetic peptide containing the DT T1 motif blocked this interaction.…”
Section: β Cop Functions As a Ctfsupporting
confidence: 52%
“…Indeed, it has been shown that for several toxins (e.g., diphtheria toxin, anthrax lethal factor, anthrax edema factor), the entry process is facilitated in vivo by specific interactions with dedicated cytosolic factors, such as the coatomer I complex, Hsp90, or thioredoxin reductase, which recognize specific amino acid sequences within the toxin polypeptide chains (44)(45)(46)(47). These interactions likely contribute to pull the catalytic chains of these toxins through the membrane through a Brownian ratchet-like mechanism (48), and could aid toxin refolding within the cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that LF N unfolding in the early endosome (pH 6.5), but not the late endosome (pH 5), is facilitated by the endosomal chaperone GRP78 (8). Furthermore, translocation of LF N -DTA from isolated endosomes requires the COPI coatamer complex, in addition to other, previously unidentified, cytoplasmic factors (9). The related AB toxins diphtheria and Clostridium botulinum C2 toxin share a requirement with LT for the COPI complex; however, unlike LT, diphtheria, C. botulinum C2 toxin, Clostridium difficile transferase, and Clostridium perfringens iotatoxin also require heat shock protein 90 (Hsp90) and cyclophilin A (26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…However, we have previously shown that the endosomal chaperone GRP78 (78 kDa glucose regulated protein) facilitates LF N unfolding in the mildly acidic early endosome (pH 6.5), but not the late endosome (pH 5) (8). Furthermore, translocation of the fusion protein LF N -DTA (LFN fused to diphtheria toxin fragment A) from endosomes in vitro requires cytosolic factors, including the coatomer protein complex I (COPI) (9). Thus, host factors clearly play an important role in toxin translocation, reflecting remarkable coevolution of a pathogen and the host.…”
Section: Tcp-1 | Tricmentioning
confidence: 99%